Some Fixed Point of Hardy-Rogers Contraction in Generalized Complex Valued Metric Spaces - Inchan, Issara; Deepan, Urairat (Communications in Mathematics and Applications, 2019)
In this work, we defined the generalized complex valued metric space for some partial order relation and give some example. Then we study and established a fixed point theorem for general Hardy-Rogers contraction. The results extend and improve some results of Elkouch and Marhrani [5].
Keywords: General Kannan condition; Hardy-Rogers contraction; Class of generalized complex valued metric space